Analisis Perbandingan Metode Marker dan Markerless Angka 0-9 3D Pada Teknologi Augmented Reality - Mulia, Yudhi Bahtera; Bangun, Eka Uliyanti Putri Br (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
In the current era, which is growing rapidly and has a very significant impact, various types of new discoveries are present and bring solutions to every problem that exists in everyday life. With this very rapid technological development, the learning process has also undergone several changes, which used to be the learning process only by using books, newspapers, now we can use smartphones that we use every day, especially now there is a very interesting technology called Augmented Reality. With Augemnted Reality technology, educators can implement AR in the teaching and learning process. The method used in this study is to analyze the comparison between the marker based tracking method and the markerless method contained in Augmented Reality. This study will focus on the effect of light intensity and detection distance on the success of the two methods in generating 3D objects in the form of numbers. The result of this trial is that the average distance from the minimum detection is 8 cm while the average maximum detection distance is 83.5 cm which has been obtained through the marker based tracking method. Whereas the markless method has an average distance of minimum detection of 4.2 cm and an average distance of maximum detection of 300 cm. The whole system can display objects with an intensity of 97 lux -1605 lux.